Factors That Affect the Indebtedness of Urban Households - A Study in the Klang Valley Malaysia - Abu Bakar, Norlaila; Mahzan, Akwa bin; Mohd Asri, Norain; Mohd Salleh, Norlida Hanim; Al-Hadi, Azrina Abdullah; Chamburi, Norshamliza (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2024)
This research uses exploratory factor analysis to identify the reliability on household debt. 332 respondents participated in this research to understand their knowledge on household debt concept and the reason they indebtness. In this context, household debt is defined as repayment to creditors regardless of the source of the loan owed. The concept of household debt is so broad based on the type of debt incurred by the respondents and its impact on the expenditure of household needs. Therefore, this research also measured the level of financial behavior, indebtedness, awareness of indebtedness and understanding of financial digitization among respondents. The purpose was to identify that respondents were inclined toward household debt (pro-debt) or vice versa. This study found that household debt has emerged as a pressing issue among Malaysians, particularly in the densely populated Klang Valley. Many residents here acquire debt primarily to cover essential living expenses and contend with the urban area's high cost of living. Keywords: Household indebtness, Consumption, Indebtness, Financial literacy, Financial digitalization